Reinforcing cycling stability and rate capability of LiNi0.5Mn1.5O4 cathode by dual-modification of coating and doping of a fast-ion conductor. (April 2018) - Deng, Yunlong; He, Lihua; Ren, Juan; Zheng, Qiaoji; Xu, Chenggang; Lin, Dunmin
Graphical abstract: Highlights: Li2 SiO3 -modified LiNi0.5 Mn1.5 O4 with well-defined octahedral morphology have been controllably obtained. The combination of the modification of fast ions conductor and solid state method will be an optional method. The cyclic performance and rate capability of LiNi0.5 Mn1.5 O4 -based materials have been significantly improved. Abstract: A simple solid state method was utilized to synthesize excellent spinel Li2 SiO3 -modified LiNi0.5 Mn1.5 O4 cathodes. Dual-modification of coating and doping of fast-ion conductor Li2 SiO3 leads to stable crystal structure and additional three-dimensional (3-D) channels for Li + -ion diffusion, and protects the electrode surface from electrolyte attack. The Li2 SiO3 -modified material possesses coexistence of ordered P 43 32 and disordered Fd- 3 m phases. As a result of improved structure, morphology and conductivity, the Li2 SiO3 -modified LiNi0.5 Mn1.5 O4 shows more superior cyclic performance, rate capability and high temperature stability than the pristine: capacity retention of 95.17% at 0.1 C after 100 cycles vs . that of 79.23%; rate capability of 130–89.1 mAh g −1 at 0.1–10 C vs . that of 120–57.6 mAh g −1 ; and high temperature capacity retention of 99.42% at 0.1 C vs . that of 79.59%. Our study provides a facile approach to stabilize crystal structure, optimize morphology and conductivity, and thus enhance electrochemical performance of LiNi0.5 Mn1.5 O4 -based materials.